Glycinergic transmission in the mammalian retina - Wässle, Heinz; Heinze, Liane; Ivanova, Elena; Majumdar, Sriparna; Weiss, Jan; Harvey, Robert J.; Haverkamp, Silke (Frontiers in Molecular Neuroscience, 2009)
Abstract Glycine and γ-aminobutyric acid (GABA) are the major inhibitory neurotransmitters in the retina. Approximately half of the amacrine cells release glycine at their synapses with bipolar, other amacrine, and ganglion cells. Glycinergic amacrine cells are small-field amacrine cells with vertically oriented dendrites and comprise more than ten different morphological types. The retinal distributions of glycine receptor (GlyR) α1, α2, α3 and α4 subtypes have been mapped with subunit-specific antibodies. GlyRs were clustered at postsynaptic hot spots which showed selective distributions for the different subunits. As a rule, only one α subunit was expressed at a given postsynaptic site. The kinetic properties of GlyRs were measured by recording spontaneous inhibitory postsynaptic currents (sIPSCs) from identified retinal neurons in wild-type, Glra1spd-ot, Glra2 and Glra3 knockout mice. From observed differences of sIPSCs in wild-type and mutant mice, the cell-type specific subunit composition of GlyRs could be defined. OFF-cone bipolar cells and A-type ganglion cells receive prominent glycinergic input with fast kinetics that is mainly mediated by α1β GlyRs (decay time constant tau 5 ms). By contrast, AII amacrine cells express α3β GlyRs with medium fast kinetics (tau 11 ms). Narrow-field (NF) and wide-field amacrine cells contain predominantly α2β GlyRs with slow kinetics (tau 27 ms). Lastly, ON-starburst, narrow-field and wide-field amacrine cells in Glra2 knockout mice express α4β GlyRs with very slow kinetics (tau 70 ms).